2017
DOI: 10.1088/1475-7516/2017/05/015
|View full text |Cite
|
Sign up to set email alerts
|

Testing ΛCDM at the lowest redshifts with SN Ia and galaxy velocities

Abstract: Peculiar velocities of objects in the nearby universe are correlated due to the gravitational pull of large-scale structure. By measuring these velocities, we have a unique opportunity to test the cosmological model at the lowest redshifts. We perform this test, using current data to constrain the amplitude of the ``signal'' covariance matrix describing the velocities and their correlations. We consider a new, well-calibrated ``Supercal'' set of low-redshift SNe Ia as well as a set of distances derived from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 82 publications
5
105
0
Order By: Relevance
“…In Fig. 9, we also compare the measured f σ 8 , including our f σ 8 measurements and those from a small selection of recent surveys (Blake et al 2011;Beutler et al 2012;Carrick et al 2015;Howlett et al 2017b;Alam et al 2017;Huterer et al 2017;Adams & Blake 2017;Shi et al 2018;Dupuy et al 2019), to the theoretical prediction. Although these measurements are all largely in agreement with the GR prediction, there is some hint of tension when they are all taken together.…”
Section: Comparison With Theorymentioning
confidence: 97%
See 2 more Smart Citations
“…In Fig. 9, we also compare the measured f σ 8 , including our f σ 8 measurements and those from a small selection of recent surveys (Blake et al 2011;Beutler et al 2012;Carrick et al 2015;Howlett et al 2017b;Alam et al 2017;Huterer et al 2017;Adams & Blake 2017;Shi et al 2018;Dupuy et al 2019), to the theoretical prediction. Although these measurements are all largely in agreement with the GR prediction, there is some hint of tension when they are all taken together.…”
Section: Comparison With Theorymentioning
confidence: 97%
“…Both Huterer et al (2017) and Howlett et al (2017b) used similar techniques to Adams & Blake (2017) but for the velocity field alone. Like Adams & Blake (2017), Huterer et al (2017) used 6dFGSv to measure f σ 8 , but include an additional 164 Type Ia supernovae (SNIa) into their data set. The total number of SNIa they have used is small, however the precise distance estimates significantly improve the measurement error of f σ 8 , even comparing to Adams & Blake (2017).…”
Section: Detailed Comparison With Other Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamaus et al 2016;Achitouv et al 2017;Hawken et al 2017), and from other different tracers of the peculiar velocity field (e.g. Percival et al 2004;Davis et al 2011;Feix et al 2015;Huterer et al 2017;Adams & Blake 2017). Moreover, it has been shown that RSD provide a powerful probe to constrain the mass of relic cosmological neutrinos (Marulli et al 2011;Upadhye 2019) and the main parameters of interacting DE models (Marulli et al 2012a;Costa et al 2017), as well as helping in breaking the degeneracy between modified gravity and massive neutrino cosmologies (Moresco & Marulli 2017;Wright et al 2019;García-Farieta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…estimated the power spectrum by first reconstructing the density field on a grid from a set of PV measurements. Many studies (Zaroubi et al 1997;Macaulay et al 2012;Johnson et al 2014;Howlett et al 2017b;Huterer et al 2017) have also successfully used a likelihood based method to estimate the velocity power spectrum from existing datasets. This was extended in Adams & Blake (2017) to include measurements of the galaxy density power spectrum, and the cross-power spectrum between the density and velocity fields.…”
Section: Introductionmentioning
confidence: 99%